(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Anita Desai, a leading figure in contemporary Indian English fiction, has garnered widespreadacclaim from Indian and international abstract circles, and her books have carved out a unique niche in thefield of Indo-Anglian writing thanks to their eccentricity and idiosyncratic beauty. Affectability instructuring the pattern of her books, uprightness of masterful vision, creative brain, sharp perception,sharp mindfulness, and capable craftsmanship have made her a much sought-after essayist, pursued bydistributors and readers alike. Only her hopes and desires, her blunders and disappointments, arereflected in her fiction. and the study in which disscused about Existentialism, Anita Desai TheNovelist, Critical Analysis Of Anita Desai , Anita Desai’s Treatment Of Feminism, Maya’ As TheRepresentative Of Post-Modern Feminism, Sita’ As The Embodiment Of Indian Feminism, Definition OfTradition And Modernity, Anita Desai – Life And Works, Existentialism In Anita Desai’s Fiction